Tailored Molecular Design for Supramolecular Network Engineering on a Silicon Surface. Issue 5 (18th February 2013) - Makoudi, Younes; Baris, Bulent; Jeannoutot, Judicael; Palmino, Frank; Grandidier, Bruno; Cherioux, Frederic
<x xml:space="preserve">Abstract</x> An open‐and‐shut case: By using tailored molecules, the formation of open or close‐packed supramolecular network can be achieved on a silicon‐based surface. The role of molecule–molecule interactions and molecule–substrate interactions to control the geometry of organic network on semi‐conductor surface is investigated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>